ENDOVASCULAR TREATMENT STRATEGIES FOR DIABETIC FOOT COMPLICATIONS IN PATIENTS WITH COEXISTING CORONARY ARTERY DISEASE - Kamalov, S.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Diabetic foot syndrome (DFS), particularly in its ischemic and neuroischemic forms, is a major cause of amputation and mortality in patients with type 2 diabetes mellitus. When combined with coronary artery disease (CAD), the risks of poor outcomes increase substantially. Endovascular revascularization has emerged as a preferred approach for limb salvage, yet clinical results vary depending on cardiovascular status and timing of intervention. Methods: This review summarizes the current literature on endovascular management of diabetic foot complications in patients with coexisting CAD. It focuses on treatment sequencing, procedural access, revascularization efficacy, and patient selection. Clinical challenges and future directions for personalized intervention algorithms are also discussed. Results: Patients with advanced DFS and concomitant CAD often require careful risk stratification before revascularization. Factors such as ejection fraction, anatomical accessibility, ulcer staging, and coronary reserve influence outcomes. Studies support the efficacy of limb-first or heart-first strategies depending on individual risk profiles. Preprocedural planning and coordinated care are essential to reduce amputation rates, repeat interventions, and perioperative complications. Conclusion: Endovascular treatment offers promising outcomes for patients with diabetic foot complications and CAD when applied within a structured, risk-oriented framework. Personalized decision-making, based on cardiac status and ischemic severity, should guide therapeutic priorities to maximize limb preservation and survival.